Benta Wawasan Sdn. Bhd.: Seraya Estate - Mohd Sharan, Abdul Lajip (Universiti Teknologi MARA, Sarawak, 2016)
As a student of Diploma in Planting Industry Management, we are required to doing our practical session for the last semester. Practical is the last subject that a compulsory need to be done by the student before they have their diploma. Practical need to be completed in three months, we are given credit hour six hour for this subject and later need to be presented for the evaluation. The practical training is a must be done for every student to make them have their own experiences in doing the work in the field of what had applied for their practical session. In the class, students only learn about the theories without doing practical. By doing the practical session, students can train themselves to doing work in real working condition and try to apply their knowledge about the plantation that has been learned in the class.